Comparison of a Deep Learning Algorithm vs. Humans for Vertebral Heart Scale Measurements in Cats and Dogs Shows a High Degree of Agreement Among Readers - Boissady, Emilie; De La Comble, Alois; Zhu, Xiajuan; Abbott, Jonathan; Adrien-Maxence, Hespel (Frontiers in Veterinary Science, 2021)
Heart disease is a leading cause of death among cats and dogs. Vertebral Heart Score (VHS) is one tool to quantify radiographic cardiac enlargement and to predict the occurrence of congestive heart failure. The aim of this study was to evaluate the performance of artificial intelligence (AI) performing VHS measurements when compared to two board-certified specialists. Ground truth consisted of the average of constituent VHS measurements performed by board-certified specialists. Thirty canine and 30 feline thoracic lateral radiographs were evaluated by each operator, using two different methods for determination of the cardiac short axis on dogs’ radiographs: the original approach published by Buchanan and the modified approach proposed by the EPIC trial authors, and only Buchanan’s method for cats’ radiographs. Overall, the VHS calculated by the AI, radiologist and cardiologist had a high degree of agreement in both canine and feline patients (ICC=0.998). In canine patients, when comparing methods used to calculate VHS by specialists, there was also a high degree of agreement (ICC=0.999). When evaluating specifically the results of the AI VHS vs the two specialists’ readings the agreement was excellent for both canine (ICC=0.998) and feline radiographs (ICC=0.998). Performance of AI trained to locate VHS reference points agreed with manual calculation by specialists in both cats and dogs. Such a computer-aided technique might be an important asset for veterinarians in general practice to limit interobserver variability and obtain more comparable VHS reading over time.